1998
DOI: 10.1111/j.2042-3306.1998.tb04491.x
|View full text |Cite
|
Sign up to set email alerts
|

Gross, histological and histomorphometric features of the navicular bone and related structures in the horse

Abstract: Summary Forelimb navicular bones and associated soft tissues were collected from 3 groups of horses and subjected to pathological examinations. The groups consisted of 38 horses with clinical navicular disease (ND) and 2 control groups, with no history of forelimb lameness, consisting of 25 age‐matched mature horses (A‐MC) and 9 immature horses (IC). Histological and histomorphometric studies were performed on tissue samples from 10 ND, 10 A‐MC and 5 IC horses. Gross changes seen only in ND horses included: fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
147
5
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(163 citation statements)
references
References 23 publications
9
147
5
2
Order By: Relevance
“…In 1998, Wright and others described core lesions of the deep digital flexor tendon, and fibrillation of the dorsal border of the tendon, in a postmortem study of horses with navicular syndrome (Wright and others 1998). Attempts to image these lesions were made ultrasonographically, and it proved technically possible to achieve images of the deep digital flexor tendon, both distal to the navicular bone, and proximal to it (Hauser and others 1982, Kristoffersen and Thoefner 2003, Sage 2002).…”
mentioning
confidence: 99%
“…In 1998, Wright and others described core lesions of the deep digital flexor tendon, and fibrillation of the dorsal border of the tendon, in a postmortem study of horses with navicular syndrome (Wright and others 1998). Attempts to image these lesions were made ultrasonographically, and it proved technically possible to achieve images of the deep digital flexor tendon, both distal to the navicular bone, and proximal to it (Hauser and others 1982, Kristoffersen and Thoefner 2003, Sage 2002).…”
mentioning
confidence: 99%
“…Such lesions have not yet been characterised histologically and their etiology remains speculative, but recent evidence suggest that their presence is associated with degenerative changes in the impar ligament (Dyson et al 2010). In recent postmortem studies, osseous fragments associated with a defect in the distal margin of the navicular bone were more common in horses with navicular disease than in age-matched controls (figures 3a and 3b) (Busoni et al 2005;Schramme et al 2005;Blunden et al 2006;Wright et al 1998). Histologically, distal border fragments have variously been described as avulsion fractures, separate centers of ossification, osseous metaplasia of the impar ligament or synovial osteoma but pathological evidence elucidating their pathogenesis remains elusive.…”
Section: Navicular Bonementioning
confidence: 99%
“…They were initially described with equal frequency in horses with clinical navicular disease and agematched control horses (Wright et al 1998). Although it was suggested that these vascular changes could be age-related (Wright et al 1998), larger and later pathological studies have found that vascular changes in the DDFT were significantly more common in the DDFT of horses with foot pain (Busoni et al 2005;Blunden et al 2006 b;Blunden et al 2009). It was therefore proposed that vascular thrombosis and occlusion could result in matrix changes that predispose horses to injury of the distal portion of the DDFT (Blunden et al 2006 b).…”
Section: Deep Digital Flexor Tendon (Ddft)mentioning
confidence: 99%
See 2 more Smart Citations